Study of internalization and viability of multimodal nanoparticles for labeling of human umbilical cord mesenchymal stem cells - Miyaki,Liza Aya Mabuchi (2012)
OBJECTIVE: To analyze multimodal magnetic nanoparticles-Rhodamine B in culture media for cell labeling, and to establish a study of multimodal magnetic nanoparticles-Rhodamine B detection at labeled cells evaluating they viability at concentrations of 10µg Fe/mL and 100µg Fe/mL. METHODS: We performed the analysis of stability of multimodal magnetic nanoparticles-Rhodamine B in different culture media; the mesenchymal stem cells labeling with multimodal magnetic nanoparticles-Rhodamine B; the intracellular detection of multimodal magnetic nanoparticles-Rhodamine B in mesenchymal stem cells, and assessment of the viability of labeled cells by kinetic proliferation. RESULTS: The stability analysis showed that multimodal magnetic nanoparticles-Rhodamine B had good stability in cultured Dulbecco's Modified Eagle's-Low Glucose medium and RPMI 1640 medium. The mesenchymal stem cell with multimodal magnetic nanoparticles-Rhodamine B described location of intracellular nanoparticles, which were shown as blue granules co-localized in fluorescent clusters, thus characterizing magnetic and fluorescent properties of multimodal magnetic nanoparticles-Rhodamine B. CONCLUSION: The stability of multimodal magnetic nanoparticles-Rhodamine B found in cultured Dulbecco's Modified Eagle's-Low Glucose medium and RPMI 1640 medium assured intracellular mesenchymal stem cells labeling. This cell labeling did not affect viability of labeled mesenchymal stem cells since they continued to proliferate for five days.